Pengelolaan dan Pemanfaatan Aset Desa Pasir Sunur Kota Pariaman - Prilly Putri Sephia; Jumiati Jumiati (PUBLICNESS: Journal of Public Administration studies, 2022)
This research has the aim to find out the Management and Utilization of Assets of Sunur Village Of Pariaman City, as well as the obstacles that will be faced in the Management and Utilization of Assets of Pasir Sunur Village of Pariaman City. The research was conducted using qualitative methods and descriptive approaches. The background of this study explains several problems, namely; It has not been well managed and utilized in the assets of Pasir Sunur Village, abandoned fish auction and fish cultivation in Pasir Sunur Village, and there are no regulations governing the management and utilization of village assets. The collection of research informants uses purposive sampling techniques where the informant is a person who knows how the overall condition of the Management and Utilization of Assets of Sunur Village of Pariaman City. Test the validity of the data using triangulation techniques. Data collection is done by means of interviews, documentation studies, and observations. The results explained that there are still some things that are not done in accordance with the rules that village assets are not well managed existing procedures, the utilization of village assets has not been used optimally and there are still some utilization systems that have not been realized. Obstacles such as low quality of human resources, lack of awareness and community participation, and lack of facilities and infrastructure in the Management and Utilization of Assets of Pasir Sunur Village Pariaman City